Prevalence and antibiotic susceptibility pattern of methicillin-resistant Staphylococcus aureus isolated from bovine raw milk in Njombe region, Tanzania - George Sanga; Athumani Lupindu; Abubakar Hoza (German Journal of Veterinary Research)
The emergence of methicillin-resistant Staphylococcus aureus (MRSA) creates a serious public health concern due to its ability to colonize and infect humans and animals. This cross-sectional study investigated the prevalence, antibiotic susceptibility pattern of S. aureus and MRSA isolated from bovine raw milk in the Njombe region, Tanzania. A total of 470 samples, including 389 raw milk samples collected at farm level, 57 raw milk samples from bulk milk-can at collection centers, and 24 swab samples from bulk milk cans. The samples were cultured on mannitol salt agar, presumptive colonies were sub-cultured onto blood agar for the isolation of S. aureus which was subsequently preliminarily confirmed using microbiological and biochemical tests. Further, confirmation of isolates was done using conventional PCR targeting gltB gene for S. aureus and mecA gene for MRSA which was later sequenced. Isolates were tested for antibiotic susceptibility by using the disc agar diffusion method. The overall prevalence of S. aureus in the study was 22.6% (106/470), with 2.9% (14/470) being MRSA. Both S. aureus and MRSA showed high resistance to penicillin (74%, 8.5%) and ampicillin (78%, 11.3%), respectively. A total of 81 (77%) isolates were resistant to at least one antibiotic and 14 isolates (13.2%) showed multidrug-resistant (MDR); with frequent antibiotic resistance patterns being to cefoxitin, penicillin, ciprofloxacin, tetracycline, and erythromycin. In conclusion, the prevalence and the MDR patterns exhibited by S. aureus and MRSA observed in this study provide baseline data for planning mitigation measures to safeguard public health.